1998
DOI: 10.1046/j.1365-2796.1998.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and urinary excretion of the coffee diterpenes cafestol and kahweol in healthy ileostomy volunteers

Abstract: de Roos B, Meyboom S, Kosmeijer-Schuil TG, Katan MB (Wageningen). Absorption and uri-nary excretion of the coffee diterpenes cafestol and kahweol in healthy ileostomy volunteers. J Intern Med 1998; 244: 451-60. Objectives. To determine the absorption and urinary excretion of the cholesterol-raising coffee diterpenes cafestol and kahweol in humans. Subjects and design. Nine healthy ileostomists consumed a dose of one, two or three cups of French-press coffee together with a standardized breakfast on three separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The metabolism of cafestol and kahweol in humans is poorly documented. An intervention study in ileostomy volunteers showed that both are well absorbed in the small intestine but little is excreted as conjugates of glucuronic acid or sulfate in urine, suggesting other metabolic routes such as oxidation [30]. Oxidation of the primary alcohol of kahweol with subsequent glucuronidation of this alcohol was the first biotransformation predicted by Meteor software, supporting our tentative identification.…”
Section: Discussionsupporting
confidence: 74%
“…The metabolism of cafestol and kahweol in humans is poorly documented. An intervention study in ileostomy volunteers showed that both are well absorbed in the small intestine but little is excreted as conjugates of glucuronic acid or sulfate in urine, suggesting other metabolic routes such as oxidation [30]. Oxidation of the primary alcohol of kahweol with subsequent glucuronidation of this alcohol was the first biotransformation predicted by Meteor software, supporting our tentative identification.…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, despite substantial research on caffeine, trigonelline, and phenolic compounds [ 33 ], there is a lack of fundamental knowledge on this critical topic, even more when it comes to different patterns of consumption including the number of daily servings and repeated daily doses, which represents a common scenario among coffee consumers. In addition, the circulating metabolites derived from coffee diterpenes [ 35 , 68 , 69 ], potent cholesterol-raising compounds, are still unknown. This information is paramount to draw a more realistic physiological picture and, hence, to better understand the biological properties of long-term coffee consumption [ 33 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, oral administration of melatonin via the drinking water was also reported to be effective in suppressing 7,12-dimethylbenzanthracene-induced mammary tumor growth [39]. In addition, for adults consuming moderate amounts of coffee (3-4 cups/day providing 300-400 mg/day of caffeine), there is little evidence of health risks and some evidence of health benefits [40]. A number of clinical and basic studies are required to establish the effects of melatonin on certain cancer.…”
Section: Discussionmentioning
confidence: 99%